Cooperative targeting of PARP-1 domains to regulate metabolic and developmental genes - Bamgbose, Gbolahan; Johnson, Sarah; Tulin, Alexei (Frontiers in Endocrinology, 2023)
PARP-1, also known as poly(ADP-ribose) polymerase 1, is a multifunctional nuclear enzyme that plays a critical role in transcriptional regulation through its three functional domains: the N-terminal DNA-binding domain (DBD) containing two zinc fingers for DNA binding and a third zinc finger for maintaining interdomain contacts, the automodification domain (AD), and the C-terminal domain, which includes the protein-interacting WGR domain and the catalytic domain. Despite the critical role that PARP-1 plays in regulating gene expression, the mechanisms by which it is targeted to chromatin are not well understood. In this study, we aimed to understand the targeting of PARP-1 to chromatin using ChIP-seq of YFP-tagged deletional isoforms of PARP-1 (ZnI, ZnII, AD-WGR) and a construct that lacks only ZnI (ΔZnI). Our results indicate that other PARP-1 domains are sufficient to target PARP-1 to active genes in the absence of ZnI. Furthermore, we found that PARP-1 represses metabolic gene pathways and activates developmental gene pathways. The results of ChIP-seq analysis showed that PARP-1 and ΔZnI were preferentially bound to the gene bodies of PARP-1-regulated metabolic genes compared to developmental genes. PARP-1 domains (ZnI, ZnII and AD-WGR) also preferentially occupied the gene bodies of PARP-1-regulated metabolic genes, however, they were more enriched at the TSS of PARP-1-regulated developmental genes compared to metabolic genes. Thus, we propose that PARP-1 domains cooperatively target PARP-1 to PARP-1-regulated genes to coordinate metabolic and developmental gene expression programs.